Keragaan dan Produktivitas Beberapa Varietas Unggul Baru Padi di Lahan Sawah Bukaan Baru Provinsi Jambi - Jumakir, Jumakir; Adri, Adri; Rustam, Rustam (Seminar Nasional Lahan Suboptimal, 2019)
Jumakir J, Adri A, Rustam R. 2019. Performance and Productivity of Some Rice Superior Variety in the New Rice Field Jambi Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 478-486. Palembang: Unsri Press.This study aims to see the performance and productivity of rice in Inpari 30, Inpari 32, Inpari 33 and Inpara 3 varieties in new paddy fields through integrated crop management (ICM). The assessment was carried out Rasau Village, South Pamenang Subdistrict, Merangin District, Jambi Province in June-October 2018 with an area of 1 ha. The location of the study is the printing of new paddy fields and locations in basin areas on oil palm plantations. The varieties used are Inpari 30 Varieties, Inpari 32, Inpari 33 and Inpara 3. Varieties used are Inpari 30, Inpari 32, Inpari 33 and Inpara 3. Varieties of technology with ICM approach include new variety superior, seedling age 21 days, number of seedlings 2-3 stems/clump, and planting system of jajar Legowo 4: 1 with spacing 25 cm x 25 cm. Granting Agrimeth as a seed treatment. The dosage of fertilizer given is 150 kg Urea/ha, 100 kg SP-36/ha, 50 kg KCL/ha. The results of the study showed that the percentage of plant growth of several rice varieties in the nursery showed good growth with a percentage of growing more than 80 percent. The growth of rice plants in the vegetative phase and the generative phase showed considerable performance. Of the four varieties, it was seen that Inpari 30 showed better performance, followed by Inpari 32 varieties, Inpara 3 and Inpari 33. The pests that appeared were brown planthopper pests. Inpari 30 rice productivity is 7.45 t/ha, Inpari 32 is 6.71 t/ha and Inpara 3 is 6.42 t/ha while Inpari 33 rice productivity is 6.13 t/ha. Increased productivity of Inpari 30 rice was 9.93% - 17.72% compared to Inpari 32, Inpari 33 and Inpara 3.Keywords: ICM technology , new rice, new land